A digital inclusion: Empowering all Australians - Walton , Peter (Journal of Telecommunications and the Digital Economy, 2019)
Digital technologies now pervade every aspect of modern Australian society. Almost every aspect of how we live, work and play – from getting an education, accessing health care, communicating with friends to getting a job – is influenced by digital technology. In this era of rapid change, the trajectory of economic development, our future prosperity and our ambitions to be a socially inclusive nation will all be influenced by the increasing growth and reliance on digital technologies as a part of everyday life. Digital inclusion (and equality) is increasingly becoming one of the major social justice challenges of our time. Digital inclusion is vital to employment participation, economic development, educational achievement, social and civic inclusion, health and wellbeing.Many people continue to be digitally excluded in Australia and, importantly, as technology changes there is a growing risk of a participation gap in terms of a person’s ability to engage with technology. At present, the response to such a major issue in Australia is fragmented and only occasionally addressed holistically. Comprehensive national research on this issue is limited, the longer-term costs of digital exclusion have not been fully explored, nor do we have a national plan to mobilise a whole of community effort that ensures that all Australians have the skills and opportunity to benefit from digital citizenship.The purpose of this paper is to explore the current needs, challenges and benefits of digital inclusion in Australia. It explores how the concept of inclusion is evolving with changes in technology and to social structures. This article is a précis of a White Paper commissioned by Telstra. The aim is to advance our understanding of digital inclusion and introduce a more refined conceptual framework for defining and addressing digital equality.